On the Stability of Some Discrete Fractional Nonautonomous Systems - Fahd Jarad; Thabet Abdeljawad; Dumitru Baleanu; Kübra Biçen (Abstract and Applied Analysis)
Using the Lyapunov direct method, the stability of discrete nonautonomous systems within the frame of the Caputo fractional difference is studied. The conditions for uniform stability, uniform asymptotic stability, and uniform global stability are discussed.